Keratinophilic fungi and other moulds associated with air-dust particles from Egypt - Abdel-Hafez, S I; Moubasher, A H; Barakat, A (Folia microbiologica, 1990)
One-hundred and eleven species and three species varieties belonging to 39 genera were collected from 50 dust samples on the five media used at 28 degrees C. Using the hair-baiting technique with horse hair, 10 species of Chrysosporium were isolated: C. asperatum, C. state of Arthroderma tuberculatum, C. indicum, C. inops, C. keratinophilum, C. merdarium, C. pannorum, C. queenslandicum, C. tropicum and C. xerophilum. True dermatophytes were isolated: Trichophyton verrucosum and Trichophyton sp. Also, numerous fungi tolerating high levels of cycloheximide were encountered, such as members of Acremonium, Aspergillus and Penicillium. On plates of glucose or cellulose Czapek-Dox agar (free from sucrose) the most frequent fungi were: Alternaria alternata, Aspergillus flavus, A. flavus var. columnaris, A. fumigatus, A. niger, A. ochraceus, A. sydowii, A. terreus, Chaetomium globosum, Cladosporium herbarum, Emericella nidulans, Fusarium oxysporum, Mucor hiemalis, Penicillium chrysogenum, P. oxalicum, Scopulariopsis brevicaulis and Ulocladium atrum. On plates of 50% sucrose or 10 and 20% NaCl-Czapek's agar, some interesting species were frequently encountered: Eurotium amstelodami, E. chevalieri, E. halophilicum, E. montevidensis, E. repens, E. rubrum and Scopulariopsis halophilica. The isolated fungi have been tested for osmophilicity and halophilicity, they showed different rates of growth on sucrose and sodium chloride-Czapek's medium of various osmotic potential.
Keywords: Osmosis; keratiny; Sodium Chloride; Chrysosporium; osmóza; zvířata; Animals; kultivační média; prach; houby; vlasy, chlupy; chlorid sodný; Hair; Keratins; koně; Dust; mikrobiologie vzduchu; Culture Media; Air Microbiology; Horses; Egypt; Fungi